A CFD-PBM approach for modeling ice slurry flow in horizontal pipes. (2nd February 2018) - Xu, Dan; Liu, Zhiqiang; Cai, Lingling; Tang, Yifang; Yu, Yunxia; Xu, Aixiang
Highlights: A CFD-PBM approach for modeling ice slurry flow in horizontal pipes was established. The comparisons between the CFD-PBM approach and CFD approach were carried out. The CFD-PBM approach was performed under various boundary conditions. The proposed CFD-PBM approach is more appropriate than CFD approach. Abstract: Understanding the flow characteristics of ice slurry is very important for designing and controlling its transportation system. In this study, a CFD-PBM approach consisting of a population balance model (PBM) and a CFD model was established to investigate ice slurry flow in the horizontal pipes. The pressure drops from the CFD-PBM approach are in good agreement with the experimental data. The numerical flow characteristics obtained from the CFD-PBM approach and the CFD approach were quantitatively compared. The results showed that the simulations from these two approaches present the same distribution features, and they are exactly similar in the main flow region. But the ice particle size, ice slurry velocity near the wall region are different, especially there is an obvious difference existing in the ice volume fraction distribution, indicating that the ice size has an obvious impact on the flow characteristics of ice slurry. The CFD-PBM approach has a unique ability to describe ice slurry flow in pipes according to the actual ice size distribution, thus the simulation by the CFD-PBM approach is more efficient. The CFD-PBM approach was also performed under various boundary conditions of ice slurry flow. The results could also correspond to the actual features. Therefore, the proposed CFD-PBM approach is more appropriate to simulate the flow behavior of ice slurry.